Suicidal behaviors and interpersonal theory of suicide constructs among adolescent girls and emerging adult women with eating disorders: the moderating role of age - Goldstein, Amit; Shachar-Lavie, Iris; Krispin, Orit; Rom, Roni; Gur, Eitan; Horesh-Reinman, Netta; Gvion, Yari (Frontiers in Psychiatry, 2025)
BackgroundIndividuals with Eating Disorders (EDs) are at an elevated risk for suicidal behaviors (SB). The aim of this study was to explore the relationship between constructs of the Interpersonal Theory of Suicide (IPTS), SB and age among individuals with EDs.MethodsThe study included 140 participants: 77 adolescent girls (ages 12-17) and 63 emerging adult women (ages 18-29). Participants completed a battery of psychological instruments assessing SB, ED symptom severity, non-suicidal self-injury (NSSI), perceived burdensomeness (PB), and thwarted belongingness (TB).ResultsPB levels were higher among emerging adults compared to adolescents while TB levels were similar across groups. PB was significantly associated with SB among adolescents, but not among emerging adults. In contrast, TB was significantly associated with SB among emerging adults, but not among adolescents. No moderating effect of age was found in the relationship between NSSI and SB.ConclusionThese findings support the contribution of IPTS constructs (TB, PB) to SB among females with ED. Moreover, the identification of age-specific mechanisms by which IPTS constructs operate provides novel insight with potential clinical implications. Interventions for adolescents with EDs and SB may benefit from caregiver-focused strategies that reduce adolescents’ sense of burdensomeness, whereas interventions for emerging adults with EDs and SB may be improved by enhancing social integration and strengthening their sense of belongingness.